Probing Neurovisceral Integration via Functional Near-Infrared Spectroscopy and Heart Rate Variability - Condy, Emma E.; Friedman, Bruce H.; Gandjbakhche, Amir (Frontiers in Neuroscience, 2020)
The neurovisceral integration model (NVM) proposes that an organism’s ability to flexibly adapt to their environment is related to biological flexibility within the central autonomic network. One important aspect of this flexibility is behavioral inhibition (Thayer & Friedman, 2002). During a behavioral inhibition task, the central autonomic network (CAN), which is comprised of a series of feedback loops, must be able to integrate information and react to these inputs flexibly to facilitate optimal performance. The functioning of the CAN is shown to be associated with respiratory sinus arrhythmia (RSA), as the vagus nerve is part of this feedback system. While the NVM has been examined through neural imaging and RSA, only a few studies have examined these measures simultaneously during the neuroimaging procedure. Furthermore, these studies were done at rest or used tasks that were not targeted at processes associated with the NVM, such as behavior inhibition and cognitive flexibility. For this reason, the present study assessed RSA and neural activation in the prefrontal cortex simultaneously while participants completed a behavior inhibition task. RSA and functional near-infrared spectroscopy (fNIRS) were collected in 38 adults and resting levels of prefrontal activation were negatively related to RSA, but prefrontal activation during the behavior inhibition task was not. The negative relationship between RSA and oxygenated hemoglobin is consistent with previous fMRI work examining the NVM at baseline and should be further studied. Additional research investigating how this relationship may change based on task demands or environmental contexts would help clarify the applicability of the model.